ANALISIS PERBEDAAN PRINSIP DAN OPERASIONAL ANTARA BANK SYARIAH DAN BANK KONVENSIONAL INDONESIA - Ilyas Yusriansah; Rafi Yulrefan; Selviyana, Selviyana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
A study on the differences in principles and operational mechanisms between Islamic banks and conventional banks in Indonesia revealed fundamental differences. Islamic banks conduct their business activities based on the principles of Islamic law, which reject the practices of usury, gharar, and maysir, and implement a profit-sharing and sales-based contract system, emphasizing fairness and transparency in every transaction. Conversely, conventional banks operate under positive legal frameworks and use the interest system as the basis for all their financial activities. From an operational standpoint, Islamic banks are not solely focused on profit maximization, but also prioritize social welfare values and equitable economic distribution. Supervision of Islamic banks is carried out by the Sharia Supervisory Board and the National Sharia Board to ensure compliance with sharia principles, while conventional banks are under the supervision of the Board of Commissioners in accordance with applicable banking regulations. The fundamental differences in these supervisory principles and systems have implications for the variation in products, services, and economic goals that are the focus of each financial institution.